Student perspectives on programmatic assessment in a large medical programme: A critical realist analysis. Issue 9 (29th April 2022) - Roberts, Chris; Khanna, Priya; Bleasel, Jane; Lane, Stuart; Burgess, Annette; Charles, Kellie; Howard, Rosa; O'Mara, Deborah; Haq, Inam; Rutzou, Timothy
Abstract: Background: Fundamental challenges exist in researching complex changes of assessment practice from traditional objective‐focused 'assessments of learning' towards programmatic 'assessment for learning'. The latter emphasise both the subjective and social in collective judgements of student progress. Our context was a purposively designed programmatic assessment system implemented in the first year of a new graduate entry curriculum. We applied critical realist perspectives to unpack the underlying causes (mechanisms) that explained student experiences of programmatic assessment, to optimise assessment practice for future iterations. Methods: Data came from 14 in‐depth focus groups ( N  = 112/261 students). We applied a critical realist lens drawn from Bhasker's three domains of reality (the actual, empirical and real) and Archer's concept of structure and agency to understand the student experience of programmatic assessment. Analysis involved induction (pattern identification), abduction (theoretical interpretation) and retroduction (causal explanation). Results: As a complex educational and social change, the assessment structures and culture systems within programmatic assessment provided conditions (constraints and enablements) and conditioning (acceptance or rejection of new 'non‐traditional' assessment processes) for the actions of agents (students) to exercise their learning choices. The emergent underlying mechanism that most influenced students' experience of programmatic assessment was one of balancing the complex relationships between learner agency, assessment structures and the cultural system. Conclusions: Our study adds to debates on programmatic assessment by emphasising how the achievement of balance between learner agency, structure and culture suggests strategies to underpin sustained changes (elaboration) in assessment practice. These include; faculty and student learning development to promote collective reflexivity and agency, optimising assessment structures by enhancing integration of theory with practice, and changing learning culture by both enhancing existing and developing new social structures between faculty and the student body to gain acceptance and trust related to the new norms, beliefs and behaviours in assessing for and of learning. Abstract : Using critical realism, this study reports on how and why balancing the interplay between learner and faculty agency, assessment structures, and the cultural system is key to developing new assessment practices.